On the solvability of a system of wave and beam equations - Juha Berkovits (Abstract and Applied Analysis)
We prove new existence results for linearly coupled system of wave and beam equations. The main concept is the matrix spectrum which is a natural extension of standard definition. Using invariant subspaces together with degree theoretic argument we obtain information about the range of the abstract operator.